Optimisation of processing methods for roasting coffee beans and classification of roasted coffee beans using multivariate analysis / Ku Madihah Ku Yaacob - Ku Yaacob, Ku Madihah (Institute of Graduate Studies, UiTM, 2015)
The aroma and flavour of coffee are developed in the roasting process. Major volatile flavour compounds identified in roasted coffee beans are pyrazines. Since the roasting process significantly affects these volatile compounds, the roasting conditions need to be optimised in ensuring the quality of roasted coffee beans. In this study, the roasting temperature and roasting time for Indonesian Arabica and Robusta coffee beans were optimised based on the concentration of selected pyrazines (2-methylpyrazine, 2,3-dimethylpyrazine, 2,5-dimethylpyrazine, 2,3,5-trimethylpyrazine and 2,3,5,6-tetramethylpyrazine) using response surface methodology (RSM), supported by overall sensory evaluation by an expert panelist and trained panelists. Since undesirable acrylamide is known to be produced during roasting process, minimising the amount of acrylamide was also considered in the optimisation of roasting process. Pyrazines were extracted using solid phase microextraction (SPME) and gas chromatgraphy with flame ionisation detector (GC-FID) while acrylamide was analysed using solid-phase extraction (SPE) and GC-FID…